Potentiality of the forage meal of Stizolobium niveum and Stizolobium aterrimum as a nutraceutical for animal feeding - Scull, Idania; Savón, Lourdes; Salabarría, Iraida Spengler; Herrera, Magalys; González Canavaciolo, V. L. (Cuban Journal of Agricultural Science, 2018)
A completely randomized design with five repetitions was used to evaluate the nutraceutical value of the forage meal of Stizolobium niveum and Stizolobium aterrimum for their use in animal feeding. The experiment was performed in September, on a brown soil with carbonate, without irrigation or fertilization. There were differences (P <0.05) between the plant materials evaluated for the nutritional and nutraceutical indicators studied. The highest values of crude protein, true protein and neutral detergent fiber were obtained for S. niveum meal (277.97, 255. 42, 625.51 g/kg DM). The content of linoleic, linolenic, stearic and palmitic acids in this meal suggests higher quality. The concentration of total carotenoids, total polyphenols, total tannins and total saponins was higher for S. aterrimum (136.08 ug/g, 25.20, 15.93 g/kg DM, 10.09 mg/100g), while the condensed tannins associated with fiber were lower (5.68 g/kg DM). The forage meal of S. niveum and S. aterrimum has high nutritional and nutraceutical value so it could favor the control of animal health, as well as improve their productivity and welfare. It is proposed to continue in vivo researchers that include meals in different formulations of diets. Key words: nutritive, mucuna, polyphenols, fatty acids, tannins, carotenoids